Blood done sign my name - Tyson, Timothy B. (New York : Random House, 2004)
The author returns to his hometown of Oxford, North Carolina, to make sense of the thirty-year-old murder of a black man by a Klansman, and the Klansman's subsequent acquittal by an all-white jury
A true story read by the author
Keywords: African Americans -- Crimes against -- North Carolina -- Oxford -- History -- 20th century; Trials (Murder) -- North Carolina -- Oxford; Murder -- North Carolina -- Oxford -- History -- 20th century; Oxford (N.C.) -- Race relations